1996
DOI: 10.1111/j.1600-0420.1996.tb00707.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of functionally intact pig retina mitochondria

Abstract: Two alternative methods for the isolation of functionally intact mitochondria from pig retina were evaluated by means of differential centrifugation. If ATP and bovine serum albumin were present during the isolation procedures mitochondria exhibited ADP sensitive respiration and membrane potentials, comparable to values from other tissues. The mitochondria fraction of both methods differed in purity, being almost free of synaptosomes when a discontinuous Ficoll gradient centrifugation was used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…We used a procedure adapted from that for adrenal cortical mitochondria separation [41] to isolate mitochondria rich-fraction from retinal tissue [42] . Briefly, each individual experiment used three pairs of mice retinas from the same experimental group.…”
Section: Methodsmentioning
confidence: 99%
“…We used a procedure adapted from that for adrenal cortical mitochondria separation [41] to isolate mitochondria rich-fraction from retinal tissue [42] . Briefly, each individual experiment used three pairs of mice retinas from the same experimental group.…”
Section: Methodsmentioning
confidence: 99%
“…In order to examine the subcellular localization of PGRMC1 in retinal membranes, tissues were fractionated to yield microsomal/plasma membrane, crude and density gradient purified mitochondria and synaptosomes (Method A, Schild et al, 1996). Since recent studies (Prokisch et al, 2004; Zischka et al, 2003) have demonstrated high purity of organelles separated by zone free flow electrophoresis (BD Biosciences), we further purified retinal mitochondria from the density gradient by ZE‐FFE according to (Zischka et al, 2003).…”
Section: Methodsmentioning
confidence: 99%